DEVELOPING THE VIRTUAL ATOMS AR LEARNING APP FOR ANDROID - Novike Bela Sumanik; Irmawaty Natsir (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
The development of technology has a significant impact on education, one of the innovative learning methods that can be applied in the digital era is augmented reality. The topic of atomic structure is one of the difficult subjects to understand and needs visualization so the development of augmented reality learning media is required. Augmented reality developed for the atomic structure topic is tailored to the needs of students, accompanied by sample questions, and materials, and can be accessed online or offline using Android. This research aims to determine the feasibility, including the validity, practicality, and effectiveness of augmented reality learning media on the atomic structure topic in an Android application. This development research method uses the ADDIE model of Analysis, Design, Development, Implementation, and Evaluation. The research instruments include validation sheets, interview guidelines, questionnaires, and pre-test & post-test exams that have been validated. The research sample consists of 90 eighth-grade students from SMPN 2 Merauke. The final result of this developmental research is a product in the form of an augmented reality atomic structure learning media application that is suitable for use and can be accessed through Android without an internet connection. The feasibility of the developed learning media is based on validity, practicality, and effectiveness. The material validation result is 82% (very valid) while the media validation is 80% (valid). The practicality test results average 84% (efficient). The effectiveness test results with an N-gain of 0.76 (high) and a percentage of 76% fall into the effective category. Therefore, it can be concluded that the product is suitable for use and there is an improvement in student understanding using augmented reality learning media.